ABREVIASI DALAM MEDIA SOSIAL INSTAGRAM - Verlin, Sri; Darwis, Muhammad; Hasjim, Munira (JURNAL ILMU BUDAYA, 2018)
This research is motivated by the increasing use of abreviation to social media instagram. This study aims to describe abreviation manifestation in social media instagram. The method used in this research, namely the method refer to the screenshot and record abreviation data. Furthermore, the sample used in this study is not dependent on quantity, but rather on quality based on the scope and depth of the problem under study. The results of this study indicate that the embodiment of abreviation consists of two, namely conventional and nonconventional abreviation. Nonconventional divided into two forms, namely plesetan and manasuka. Plesetan also consists of two terms, namely the term health and education level. Furthermore, manasuka consists of four terms, namely the naming of the day, the fruit, the Indonesian artist, and the country.